Purification and Characterization of Tracp from sera of Patients with Chronic Renal Failure - Hathama R. Hasan (Journal of Global Pharma Technology, 2018)
Background and Objective Tartrate Resistant Acid Phosphatase (TRACP) also known as type 5 acid phosphatase is a glycoprotein with basic pI , and occurring as two similar isoforms 5a and 5b with different carbohydrate content. This study aims to characterize both TRACP isoforms physico-chemically and spectrophotometrically Materials and Methods: Ion exchange chromatography was applied in order to purify TRACP isoforms (5a and 5b) from sera of control and patients with End Stage Renal Disease (ESRD). Results: The results indicated different specific activities of TRACP 5a and 5b and their proportional amounts in sera of patients with ESRD were different from that of the control group, they had approximate molecular weight of (36.8-39.3 KDa) and a basic isoelectric point equal to9.6 incontrol and patients with ESRD. The optimal pH for 5b is relatively higher than for 5a, the heparin (23 KU/L) had an inhibitory effect only on the activity of TRACP 5a, the iron content of isoform 5b was found to be one mole per one mole of enzyme, and UV spectrum of TRACP 5a was found to be different from that of TRACP 5b in both control and patients with ESRD. Conclusion: We conclude that there are differences in the characterization of both isoform TRACP 5a and 5b in sera of end stage renal disease.Keywords: TRACP, Purification, Isoform, Characterization.